Community Empowerment of MSMEs through Business Model Canvas Training and the Utilization of Digital Technology in Business Development - Siti Hajar Komariah; Ananda Risya Triani; Cindy Muhdiantini; Mega Fitri Yani (NJCOM: Community Service Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting community economic growth. However, many MSME actors still face challenges in business management, business model development, and the use of digital technology. This community service program aims to improve MSME capacity through training and mentoring on the Business Model Canvas (BMC), entrepreneurship, and digital marketing strategies. The program was conducted with Wahana Bina Insani in Bandung Regency using a participatory approach, including needs identification, training, hands-on practice, and evaluation. The materials covered business model concepts, the nine elements of BMC, branding, social media use, and digital content creation. Participants practiced developing their own business models based on their enterprises. The results showed improved understanding of structured business planning, customer segmentation, value creation, and digital marketing utilization. This program is expected to enhance MSME adaptability and competitiveness in the digital economy era.